48.9k views
3 votes
Write the standard form of the quadratic equation modeled by the points shown in the table below.

Write the standard form of the quadratic equation modeled by the points shown in the-example-1
User Matt Dell
by
5.3k points

2 Answers

3 votes

Answer:

The required equation is
-3x^2+11x-6

Explanation:

Consider the provided table.

As we know the standard form of the quadratic equation is
y=ax^2+bx+c

Substitute x=0 and y=-6 in above standard equation.


-6=a(0)^2+b(0)+c


-6=c

Substitute x=1, y=2 and c=-6 in standard equation.


2=a(1)^2+b(1)-6


2=a+b-6


a+b=8


a=8-b

Substitute x=2, y=4 and c=-6 in standard equation.


4=a(2)^2+b(2)-6


4=4a+2b-6


4a+2b=10


2a+b=5

Substitute value of a in above equation.


2(8-b)+b=5


16-2b+b=5


b=11

Substitute the value of b in
a=8-b


a=8-11


a=-3

Hence, the required equation is
-3x^2+11x-6

User Jonas Wouters
by
6.5k points
3 votes
we know that

The Standard Form of a Quadratic Equation is
ax² + bx + c = 0

then
for x=0 y=-6
a*0² + b*0 + c = -6---------> c=-6

for x=1 y=2
a*1² + b*1 -6 = 2---------> a+b=8---------> a=8-b---------> equation 1

for x=3 y=-0
a*3² + b*3 -6 = 0---------> 9a+3b=6---------> equation 2

substituting 1 in 2
9*(8-b)+3b=6------> 72-9b+3b=6---------> 6b=66--------> b=11
a=8-11-------> a=-3
so
a=-3
b=11
c=-6
Standard Form of a Quadratic Equation is
-3x² + 11x - 6 = 0

the answer is
-3x² + 11x - 6 = 0

User Randomusername
by
5.2k points